Transcriptomic profile of the hippocampus of rat strains with contrasting nervous system excitability - Marina Pavlova; Irina Shalaginova; Natalia Dyuzhikova (PLoS ONE, 2026)
Individual variability of reactions to environmental influences which determines the range of the “reaction norm” and the possibilities of adaptation is strongly shaped by inherited properties of the nervous system, including genetically determined differences in excitability. Rat strains selectively bred for contrasting thresholds of neural system excitability provide a model for studying how such inherited differences are reflected at the molecular level. Here, we performed bulk RNA sequencing of the hippocampus in high-excitability (LT) and low-excitability (HT) rats to characterize baseline interstrain transcriptomic divergence. Differential expression analysis revealed strain-specific transcriptional profiles involving not only synapse- and plasticity-related genes, but also non-neuronal components associated with glial/immune functions, intracellular trafficking and protein processing, kinase signaling, extracellular matrix remodeling, and neurovascular regulation. Functional annotation highlighted differences in synaptic organization, neuronal projection development, cellular maintenance pathways, and tissue-level regulatory processes. The analysis motivates testable hypotheses involving synaptic/neurite organization, cellular maintenance pathways (MAPK/PI3K-linked trafficking and redox regulation), and glial/neurovascular components, to be evaluated in follow-up studies using structural and functional tissue-level measurements. This work also provides a reference for cross-model comparisons of polygenic excitability-related traits, as a reference transcriptomic profile from a long-term selective-breeding paradigm.